Prosthetic Rehabilitation of Three Dentinogenesis Imperfecta Patients using Hobo Twin Stage Technique and Implant Supported Overdenture - A Case Report - Amina; S Abirami; Geeta Rajput; Shaista Afroz; Shua Aftab (Indian Journal of Dental Research)
Rehabilitation of an attrited dentition is one of the most challenging task faced by a prosthodontist which requires a systematic, phase wise approach. Hobo’s techniques and Pankey Mann Schuyler’s philosophy are widely used and documented for full mouth rehabilitation. If along with attrition and discoloration teeth are also periodontally compromised, then the extraction of teeth followed by fabrication of complete denture either implant supported or mucosa supported is the only treatment option. In this case series, we have reported three cases of same family with Dentinogenesis Imperfecta, two cases presented with the severely worn dentition, poor aesthetics and difficulty in chewing. To rehabilitate these cases, Hobo’s twin stage technique had been adopted and one case had periodontally compromised teeth along with faulty prosthesis in addition to Dentinogenesis Imperfacta, so removal of faulty prosthesis, full mouth extraction followed by implant supported overdenture was planned.